2013
DOI: 10.1111/grow.12015
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Economic Specialization of Cities: Disentangling Industrial and Functional Dimensions in the Canadian Urban System, 1971–2006

Abstract: Decreasing spatial transaction and trade costs have given rise to growing economic specialization of cities. While most studies focus on industries-the final good or service produced-as the primary manifestation of urban specialization, a growing body of literature examines functions, i.e. activities and tasks performed within a given industry or firm. This paper explores how the two dimensions (industries and functions) interact across the urban system, and their relative importance is over time. Is there a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…These results are consistent with the literature on economic specialization of cities (BADE et al, 2004;BRUNELLE, 2013;DURANTON, PUGA, 2005). Indicating that there is a pattern where large cities concentrate functions of management, research and development of companies, while small cities concentrate the production functions of companies.…”
Section: Results From Locational Quotient (Lq)supporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with the literature on economic specialization of cities (BADE et al, 2004;BRUNELLE, 2013;DURANTON, PUGA, 2005). Indicating that there is a pattern where large cities concentrate functions of management, research and development of companies, while small cities concentrate the production functions of companies.…”
Section: Results From Locational Quotient (Lq)supporting
confidence: 92%
“…It is possible, then, to state that these cities are specialized in blue-collar occupations. This functional specialization pattern, where large cities have higher proportion of white-collar occupations and small cities have higher proportion of blue-collar occupations, is according to international literature (BADE et al, 2004;BRUNELLE, 2013;DURANTON, PUGA, 2005).…”
Section: Final Commentssupporting
confidence: 52%
See 1 more Smart Citation
“…As high-paying, non-routine tasks have become more common and low-paying, routine tasks less common, the incomes of regional labor markets have been differentially affected. There is growing evidence that large metropolitan areas have benefited, and small metropolitan areas have suffered, as professional and management jobs have expanded and standardized production jobs have contracted (Brunelle 2013). Other notable topics in economic geography were not included but this is understandable because even a comprehensive volume like this cannot address everything in this wide field.…”
Section: Book Review 339mentioning
confidence: 99%
“…It has been suggested that objective criteria apply to physical, social and economic functions whereas subjective criteria refer to various aspects of personal life, such as desires, expectations, happiness and pleasure (Ozturk and Ozdemir, 2013). Accordingly, research focusing on the quality of life can be categorized by applying physical (Smith et al, 1997;Mohadeseh et al, 2015), social (Zenker and Rutter, 2014;Turksever and Atalik, 2001;Theodori, 2004;Berntze and Johannessen, 2016) and economic (Brunelle, 2013;Addanki and Venkataraman, 2017;Pratt and Hutton2013) criteria. Some studies have investigated the quality of cities in a more compherensive way (Kaklauskas et al, 2018;Węziak-Białowolska, 2016;Essam and Khalil, 2012).…”
Section: Introductionmentioning
confidence: 99%